Evaluation of geogrid reinforcement of flexible pavement performance: A review of large-scale laboratory studies. (March 2021) - Alimohammadi, Hossein; Zheng, Junxing; Schaefer, Vernon R.; Siekmeier, John; Velasquez, Raul
Abstract: Many researchers have conducted laboratory studies for assessing the interaction mechanism of soil and geosynthetics and have shown that the performance of flexible pavement is enhanced by geosynthetic reinforcement through extending their service life or decreasing the base course thickness. However, there is a lack of comprehensive comparisons between different studies. This paper reviews laboratory studies available in the literature and presents a review of the main contributions. This literature review reveals that improvement of the performance due to the geosynthetic reinforcement relates to various factors and variables, including geogrid stiffness and geometry, geogrid location/depth, asphalt surface and aggregate thicknesses, and subgrade stiffness. Based on synthesizing laboratory testing studies, a regression-based formulation is proposed to predict the Granular Equivalent (GE) factor of geogrid reinforcement of flexible pavements. The predictive model is robust as it includes the key parameters mentioned above. This formula was developed from a regression analysis by back calculating the variety of the results of the performed experimental tests using the AASHTO1993 design method to evaluate the equivalent base course thickness of reinforced sections compared to unreinforced sections. The benefit of this study is realizing and understanding the structural benefits of geogrids and applying GE factors to a pavement design to reduce the thickness of gravel and/or asphalt and consequently extend the service life and reduce maintenance costs. It is expected that the appropriate use of geogrids can be a significant cost saving per project.